Pengaruh Pengembangan Karir, Komunikasi dan Budaya Organisasi Terhadap Kinerja Pegawai - Sinurat, Jekinya Andi S.; Rahmad, Juhari; Irawan, Dodi; Nasution, Mahdayani; Tarigan, Nur M. Ridha; Nasti, Nilawati; Pane, Sri Gustina (Journal of Management and Economics Research, 2024)
The problems in this research are how is the influence of career development, communication and organizational culture partially and concurrently on the employee performance in the Kantor Wilayah DJP Sumatera Utara I? Research objectives: To determine the effect of career development, communication and organizational culture partially and simultaneously on the employee performance in the Kantor Wilayah DJP Sumatera Utara I. The hypothesis proposed is: There is a significant effect of career development, communication and organizational culture partially and jointly on the employee performance in the Kantor Wilayah DJP Sumatera Utara I. The study was conducted at the Kantor Wilayah DJP Sumatera Utara I Jalan Sukamulia No. 17A Medan, with a population of 146 people, and a study sample of 59 people. Based on the analysis results obtained career development has a effect on the employee performance of the Kantor Wilayah DJP Sumatera Utara I, this is supported by the results of t count analysis > t-table (6,644 > 2,004) at n = 59 at 95% significance level. Communication has a positif and significant effect on the employee performance of the Kantor Wilayah DJP Sumatera Utara I, this is supported by an analysis of t count > t-table (2,705 > 2,004) at n = 59 at 95% significance level. Organizational culture has a not effect on the employee performance of the Kantor Wilayah DJP Sumatera Utara I, this is supported by an analysis of t count < -table (0,740 < 2,004) at n = 59 with a significant level of 95%. Value of F-count> F table (42,435 > 2,77) This states that together (multiple) there are positive and significant effects of career development, communication and organizational culture on the employee performance of employees of the Kantor Wilayah DJP Sumatera Utara I. Thus the hypothesis proposed is accepted by the truth.